VIVÊNCIAS DE PROFISSIONAIS EM UNIDADE DE TERAPIA INTENSIVA E NÚCLEO INTERNO DE REGULAÇÃO DE LEITOS NA PANDEMIA DA COVID-19 - PEREIRA, Joelmara Furtado dos Santos (2022)
INTRODUCTION: In 2020, Brazil experienced an unprecedented health crisis, the so-called first wave of the COVID-19 Pandemic. The unexpected increase in patients with severe illness who demanded mechanical ventilators, beds and intensive care threatened the high complexity response capacity. From this perspective, this research sought to analyze the experiences of health professionals who worked in the Intensive Care Unit and in the Internal Bed Regulation Nuclei, in the context of the COVID-19 pandemic. METHODS: This is a descriptive exploratory study with a qualitative approach developed in the Intensive Care Units and Internal Bed Regulation Centers of two public hospitals, from November 2020 to January 2021, in the state of Maranhão. 22 professionals were selected, this sample was defined by the criterion of saturation of the senses. The data collection technique was the semi-structured interview. For analysis of the interviews, the technique of content analysis was used, in the thematic modality and the software NVIVO® 12 was used to aid in the organization and treatment of the data. RESULTS: Professionals reported that in the face of high demand, critically ill patients and insufficient beds, there was a need to reorganize the hospital environment and expand existing beds. Of the situations mentioned, the following stand out: the work overload and the shortage of professionals that affected the quality of care, leading to new forms of care production and the transitory rupture of the overvaluation of professional categories; the challenge of offering the expected high-standard care, which began to be built under the rhythm of uncertainty and ignorance of the disease; the feeling of professional collaboration and the perception of security in the team signaled as necessary presuppositions for the continuity of care. The experience with death and dying on a larger scale interfered in the way of facing the end of life in that context. In parallel with this overwhelming context, deciding who would occupy the intensive bed was a difficult and conflicting task, given the uncertainties of the “new disease”. Thus, a combination of clinical and non-clinical criteria was considered, evaluated on a case-by-case basis, such as severity, chance of survival, distance to be covered and transport conditions. It was identified that the context of an unknown disease, family and institutional pressures were points of tension and interfered in the decision-making process.FINAL CONSIDERATIONS: The changes that occurred in the work environment of the ICU and NIR influenced the way of dealing with that exceptional situation. Their experiences with the (re)organization of space, the meaning attributed to care and interprofessional relationships, showed that these agents were affected in a way and intensity peculiar to each one. Decision making was marked by practices and challenges arising from the context of exacerbation of the lack of beds and the knowledge that was structured about the disease, from the perspective of an arduous phenomenon and related to aspects extrinsic to the technical-assistance sphere.